ENHANCING CHILDREN’S LITERACY THROUGH CREATIVE MEDIA STRATEGY IN COMMUNITY-BASED LEARNING IN MEDAN - Lucy Khawardi; Marwah; Apriliana; Susianto; Rahmawati Hutagalung (LPPM IAD Probolinggo, 2026)
The development of children’s literacy remains a critical challenge, particularly in community-based learning contexts where access to engaging and relevant learning resources is often limited. This study investigates the effectiveness of creative media as a strategy to enhance children’s literacy in a community setting in Medan, Indonesia. Employing a Participatory Action Research (PAR) design, the study involved 25 children aged 7–12 years, along with parents and local facilitators. The intervention integrated illustrated storybooks, interactive storytelling, and literacy-based games, enriched with cultural and religious values. Data were collected through observation, interviews, documentation, and pre- and post-literacy assessments. The findings reveal significant improvements in both engagement and literacy skills. Active participation increased from 36% to 84%, while average literacy scores improved from 64% to 81%. Children also demonstrated higher motivation, longer attention spans, and greater involvement in literacy activities. In addition, 88% of children reported increased enjoyment in learning, and 90% of parents observed positive changes in their children’s reading habits at home. These results indicate that creative media serves as an effective, contextually relevant approach to literacy development by combining cognitive, social, and cultural dimensions of learning. The study contributes to the literature by extending the application of multiliteracies and sociocultural frameworks into community-based settings and highlighting theimportance of integrating local values in literacy practices.